2020
DOI: 10.3389/fmed.2020.00009
|View full text |Cite
|
Sign up to set email alerts
|

Global and Historical Distribution of Clostridioides difficile in the Human Diet (1981–2019): Systematic Review and Meta-Analysis of 21886 Samples Reveal Sources of Heterogeneity, High-Risk Foods, and Unexpected Higher Prevalence Toward the Tropic

Abstract: Clostridioides difficile (CD) is a spore-forming bacterium that causes life-threatening intestinal infections in humans. Although formerly regarded as exclusively nosocomial, there is increasing genomic evidence that person-to-person transmission accounts for only <25% of cases, supporting the culture-based hypothesis that foods may be routine sources of CD-spore ingestion in humans. To synthesize the evidence on the risk of CD exposure via foods, we conducted a systematic review and meta-analysis of studies r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 105 publications
(87 reference statements)
1
15
0
Order By: Relevance
“…COVID-19 continues to spread worldwide 2 (55), and the influx of overseas cases may introduce new transmission dynamics that are not possible to predict using current models. Studies have reported that the epidemic of some viruses (e.g., SARS-CoV) or bacteria (e.g., Clostridioides difficile) can be affected by geographical climatic factors such as temperature, humidity, and latitude (56)(57)(58), and COVID-19 infections may consequently be impacted by seasonality and latitude in unpredictable ways. However, we were not able to add additional results and analysis of temperature for COVID-19 due to lack of available data.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 continues to spread worldwide 2 (55), and the influx of overseas cases may introduce new transmission dynamics that are not possible to predict using current models. Studies have reported that the epidemic of some viruses (e.g., SARS-CoV) or bacteria (e.g., Clostridioides difficile) can be affected by geographical climatic factors such as temperature, humidity, and latitude (56)(57)(58), and COVID-19 infections may consequently be impacted by seasonality and latitude in unpredictable ways. However, we were not able to add additional results and analysis of temperature for COVID-19 due to lack of available data.…”
Section: Discussionmentioning
confidence: 99%
“…If human-originated isolates of P. distasonis can appear in chicken or other animals, then this bacterium might be able to reach humans via food and livestock, as is common among other aerobic or anaerobic foodborne or food-dwelling microbes. 27 …”
Section: History Ecology and Identificationmentioning
confidence: 99%
“…Studies on environmental contamination with C. difficile have shown a number of potential sources including soil (7,8), water (9, 10), animals (11)(12)(13), households (14) and food (15)(16)(17)(18)(19)(20), in addition to patients colonized with C. difficile (21), with cases acquiring infection through the oro-faecal route with ingestion of spores. This has been suspected due to the on December 1, 2020 at UNIV OF WESTERN AUSTRALIA M209 http://aem.asm.org/ Downloaded from overlapping of ribotypes (RTs) of C. difficile found in the environment, animals and humans (22,23).…”
mentioning
confidence: 99%